Length-weight relationships and condition factors of mono- and mixed-sex Nile tilapia (Oreochromis niloticus) in open water cage culture system - Saznzib Kumar Barman; Bhupal Ronjon Das; Mrityunjoy Kunda; Sabuj Kanti Mazumder; Md. Jasim Uddin; Partho Protim Barman (Journal of Fisheries, 2023)
The current study compared the length-weight relationships and condition factors in mono- and mixed-sex Nile tilapia (Oreochromis niloticus). The trial lasted for 91 days and included two treatments with five replications for each, all with the same stocking density. During the study period, 20 randomly selected fish individuals were measured and recorded from each cage every two weeks. The observed growth trend was allometric, with no significant difference in the mean exponential values (b), 2.696 and 2.65 for mono and mixed-sex tilapia respectively. There was a significant difference in final weight gain between monosex (171.58±7.39 g) and mixed-sex (149.09±4.14 g) tilapia. There was no significant difference in final length between monosex (19.80±0.42 cm) and mixed-sex (19.80±0.42 cm) tilapia. Moreover, the mean correlation coefficient (r2) of both groups was positive. The Fulton condition factor (K) also varies from 0.700 to 1.000 (monosex) and 1.000 to 1.010 (mixed-sex). The relative condition factor (Kn) for monosex and mixed-sex tilapia ranged from 1.96 to 2.222 and 2.092 to 2.35 respectively, indicated good aquaculture conditions. The present findings will attract fish farmers to mixed-sex tilapia culture by allowing them to lessen hormone administration and expected to boost national fish production through open water cage aquaculture.